BE_VERWALTUNGSGERICHT 100 2024 219 vom 20. Februar 2025 - BE Verwaltungsgericht (2025)
Revision des Urteils des Verwaltungsgerichts des Kantons Bern vom 27. Juni 2024 (100.2022.196) | Revision/Erläuterungen/Berichtigung